Hypertensive disorders of pregnancy among women with cardiovascular disease in Norway: A historical cohort study - Ingrid Langen; Eldrid Langesæter; Nina Gunnes; Vibeke Marie Almaas; Guttorm Haugen; Mette‐Elise Estensen; Ingvil Krarup Sørbye (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Women with cardiovascular disease may be at increased risk of hypertensive disorders of pregnancy (HDP). We aimed to: (1) Investigate the occurrence of HDP in a cohort of pregnant women with cardiovascular disease and compare it with the occurrence in the general population. (2) Assess the association between maternal cardiovascular risk and risk of HDP. Material and methods We reviewed clinical data on a cohort of 901 pregnancies among 708 women with cardiovascular disease who were followed at the National Unit for Pregnancy and Heart Disease and gave birth at Oslo University Hospital between 2003 and 2018. The exposure under study was maternal cardiovascular risk, classified as low, moderate, or high based on a modified classification by the World Health Organization. The main outcome of interest was HDP, which included pre‐eclampsia and gestational hypertension. The proportion of HDP cases in the general population in the same period was extracted from the Medical Birth Registry of Norway. We used logistic regression to estimate crude and adjusted odds ratios (OR) of HDP, with associated 95% confidence intervals (CIs), for women with moderate‐ and high cardiovascular risk compared to women with low risk. Results The occurrence of HDP in the study cohort was 12.1% (95% CI: 10.0%–14.4%) and varied between 8.7% (95% CI: 6.5%–11.3%) in the low‐risk group, 15.7% (95% CI: 11.1%–21.4%) in the moderate‐risk group, and 22.2% (95% CI: 15.1%–30.8%) in the high‐risk group. By contrast, the nationwide occurrence of HDP was 5.1% (95% CI: 5.1%–5.2%). In the study cohort, the proportions of pregnancies with gestational hypertension and pre‐eclampsia were similar (6.3% and 5.8%, respectively). Compared to pregnancies with low cardiovascular risk, the adjusted OR of HDP was 2.04 (95% CI: 1.21–3.44) in the moderate‐risk group and 2.99 (95% CI: 1.73–5.18) in the high‐risk group. Conclusions The occurrence of hypertensive disease of pregnancy in the study cohort was more than doubled compared to the general population in Norway. The risk of HDP increased with maternal cardiovascular risk group. We recommend taking into account maternal cardiovascular risk group when assessing risk and prophylaxis of HDP.